Influence of corporate governance on fees: UK evidence / Azizah Abdullah, Michael Page and Masdiah Abdul Hamid - Abdullah, Azizah; Page, Michael; Abdul Hamid, Masdiah (2012)
Given the lack of emphasize on auditor fees, the present paper investigates the implication of governance mechanisms on auditor’s fees in UK. In particular, board of directors’ inde-pendence, size, duality roles and audit committees’ independence were examined while au-dit tenure is also included to examine the impact on auditor’s independence. It proposes a theoretical framework to investigate governance mechanism and fees, which is empirically tested on a dataset of 521 FTSE350 UK companies for six years from 1999 to 2004. The finding reveals that fees are positively and significantly related to board independence. While for the size of board members, there is a significant positive relationship with audit fee and insignificant relationship with non-audit fee. Other governance variable of duality reveals insignificant association with audit and non-audit fees. The presence of independent audit committee on boards significantly reduces auditor assessment. Furthermore, the result also suggest that tenure is not as a main factor may impair auditor independence and most com-pany pay higher fees for non-audit services than statutory services. An additional analysis should be done on audit and non-audit fees by using sample from other countries and other time periods to determine the reliability and the external validity of the result.